CRIMES DIGITAIS: UMA NECESSÁRIA RELEITURA DO DIREITO PENAL À LUZ DAS NOVAS TECNOLOGIAS - Rosa Acha, Fernanda (LINKSCIENCEPLACE, 2026)
The study of this new way of criminality is relevant because it can be seen technologies advances, especially with the internet and globalization, which is capable to modify the crimes and the investigations. Following that line, study the consequences of these new way of crimes seems necessary so that it can be aligned with the penal law and processual law, increasing a rereading of some important institutes. So that, the objective of this article is situate the penal law in this new dynamic, showing the advances and practices that must be taken for the effectivity of the investigation and law appliance. This article uses the qualitative method, studying the opinions of the persons who have the knowledge of the subject, which will help to find the conclusion of the penal law to these new technologies. As a conclusion, the study will analyze the origin and evolution of internet in Brasil, following by the changes caused by the introduction of these new technologies in the behavior aspect, ending with the penal law adaptions to this new reality and the law advances in this issue.